Effect of 30 hours sleep deprivation on shooting score and corticospinal excitability in soldiers - Ahmadreza Yousefpour dehaghani; reza Gharakhanlou; zahra Rezasoltani Zahra (Shahid Beheshti University, 2019)
Purpose: In order to understand the effect of sleep disorders on nervous system-related functions, it is important to investigate the neural mechanisms behind these disorders. so the Purpose of this study was to investigate the Effect of 30 hours sleep deprivation on shooting score and corticospinal excitability of Thenar eminence muscle in soldiers. For this purpose, 11 volunteers (male) were selected from a military training center.Methods: In two stages, using Transcranial magnetic stimulation technique by Medtronic device as well as to register the shooting score by air rifle before and after 30 hours of sleep deprivation, the subjects were studied. Obtained data, with descriptive statistics and t-test were analyzed.Results: It was shown that 30 hours of sleep deprivation caused a signifi cant decrease in shooting score(p=0.003); also signifi cantly increased the range of motor evoked potential amplitude (p=0.009), no signifi cant reduction of motor evoked potential latency and no signifi cant increase in facilitated motor evoked potential latency (p=0.98, p=0.15).Conclusion: According to the results of this study it can be concluded that 30 hours of sleep deprivation, signifi cantly decreased the score of shooting, Since, any signifi cant increase or decrease in the amount of excitability affects the optimal performance of the nervous system, Therefore, it can be said that the decrease in shooting score in subjects of this study is probably related to the disturbance in the observed amount of excitability nervous system , Which can be considered in future research.